Nursing of a patient with mammary nodules of Liver-Qi stagnation syndrome treated with Chinese medicine ointment rubbing therapy combined with holographic scraping treatment (乳腺中药膏摩联合全息刮痧治疗肝郁气滞证乳癖1例的护理) - LIU Shanshan (何静); Chen Hong (陈宏) (中西医结合护理)
This paper summarized the nursing management for 1 patient with mammary nodules (hyperplasia of mammary glands) of Liver-Qi stagnation syndrome treated with Chinese medicine ointment rubbing therapy combined with holographic scraping treatment. After the syndrome of Liver-Qi stagnation was diagnosed in Traditional Chinese Medicine (TCM), TCM nursing technique was applied to this patient gradually, including Chinese medicine ointment rubbing therapy on breast and holographic scraping treatment. Dietary nursing interventions and emotional care were carried out during the treatment. Clinical results showed that the main and secondary symptoms of the patient were relieved, the pain was relieved, and the patient was satisfied with nursing service. The Chinese medicine ointment rubbing therapy combined with holographic scraping treatment gives full play to the characteristics and advantages of TCM nursing clinics, and provides reference for the design of nursing operation technique treatment scheme of mammary nodules of Liver-Qi stagnation syndrome. (本文总结乳腺中药膏摩联合全息刮痧治疗1例肝郁气滞证乳癖患者的护理经验。经中医辨证为肝郁气滞证后, 向该患者分阶段实施中医护理技术乳腺中药膏摩联合全息刮痧, 治疗期间配合饮食护理和情志护理。经干预后患者各项主、次症状得到缓解, 痛苦减轻, 患者满意度高。该护理措施充分发挥了中医护理门诊特色及优势, 为肝郁气滞证乳癖护理操作技术治疗方案设计提供参考依据。)